2015
DOI: 10.1080/02626667.2014.916407
|View full text |Cite
|
Sign up to set email alerts
|

Changes to flow regime on the Niger River at Koulikoro under a changing climate

Abstract: A significant decrease in mean river flow as well as shifts in flood regimes have been reported at several locations along the River Niger. These changes are the combined effect of persistent droughts, damming and increased consumption of water. Moreover, it is believed that climate change will impact on the hydrological regime of the river in the next decades and exacerbate existing problems. While decision makers and stakeholders are aware of these issues, it is hard for them to figure out what actions shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
1
32
1
Order By: Relevance
“…These results confirm that streamflow is vastly sensitive to both temperature and rainfall [46]. However, these results are not in agreement with the finding of Angelina et al [20] who showed an increase of mean annual flow of the Niger river basin at Koulikoro by 6.9% (2026-2050), 0.9% (2051-2075), and 5.6% (2076-2100) by using a SWAT model under the SRES A1B emissions scenario. Additionally, Azari et al [12] showed an increase in stream-flow under RCP4.5 and RCP8.5 in the Gorganroud River basin in the North of Iran.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…These results confirm that streamflow is vastly sensitive to both temperature and rainfall [46]. However, these results are not in agreement with the finding of Angelina et al [20] who showed an increase of mean annual flow of the Niger river basin at Koulikoro by 6.9% (2026-2050), 0.9% (2051-2075), and 5.6% (2076-2100) by using a SWAT model under the SRES A1B emissions scenario. Additionally, Azari et al [12] showed an increase in stream-flow under RCP4.5 and RCP8.5 in the Gorganroud River basin in the North of Iran.…”
Section: Discussioncontrasting
confidence: 53%
“…Yet, the use of the bias correction generally has the inconvenience of not taking into account the different physical laws that govern the atmosphere [53]. However, Angelina et al [20] showed that the quantile-quantile transformation can improve the simulation of extreme values. It is also necessary to take into account difficulties associated with the transfer of the parameters of the hydrological model on periods other than those where the model was calibrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of potential impacts of future climate change on water resources, as a way to recognize suitable mitigation and adaptation strategies holds utmost importance. There are many observations supporting the evidence of climate change, such as frequent occurrences of climatic extremes, rising sea level and diminishing snow packs (Amadou et al, 2014;Githui et al, 2009;Shamir et al, 2015;Yu et al, 2002). Since the climate and hydrologic cycle is inter linked, variability in climate is 15 expected to alter both the timings and magnitudes of surface runoff.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, an indubitable relation between the climate change and water resources together with the potential impacts of climatic change on water resources and hydrology has gained considerable attention in hydrologic research community (Abbaspour et al, 10 2009;Akhtar et al, 2008;Amadou et al, 2014;Gardner, 2009). The study of potential impacts of future climate change on water resources, as a way to recognize suitable mitigation and adaptation strategies holds utmost importance.…”
Section: Introductionmentioning
confidence: 99%